2004
DOI: 10.1111/j.1469-7610.2004.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Resting cortical brain activity and social behavior in higher functioning children with autism

Abstract: These observations indicate that anterior EEG asymmetry may be a marker of motivation and emotion processes that refract the autism taxon into important individual differences in social presentation among higher functioning children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
123
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(135 citation statements)
references
References 72 publications
9
123
1
1
Order By: Relevance
“…The sample size was insufficient to examine differences among children with autism, Asperger's disorder, and PDD-NOS. For example, Sutton et al (2005) reported that, compared to normally developing controls, children with high functioning autism had greater levels of self-reported social anxiety but similar levels of generalized anxiety. This limitation can be addressed in future studies with larger community samples.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was insufficient to examine differences among children with autism, Asperger's disorder, and PDD-NOS. For example, Sutton et al (2005) reported that, compared to normally developing controls, children with high functioning autism had greater levels of self-reported social anxiety but similar levels of generalized anxiety. This limitation can be addressed in future studies with larger community samples.…”
Section: Discussionmentioning
confidence: 99%
“…Neurologically, research has demonstrated decreases in activity (Dawson et al 1995;Stroganova et al 2007) and blood flow (Chiron et al 1995) in the left hemisphere; significantly increased activity in the right frontal and temporal lobes, versus controls (Kleinhans et al 2008); a lack of expected leftward structural asymmetry in gray and white matter, versus controls (Haznedar et al 2006;Lo et al 2011;Wan et al 2012); and an abnormal enlargement of the right hemisphere (Herbert et al 2005), all perhaps suggesting hyper-activation of the right hemisphere and hypo-activation of the left hemisphere in ASD (Shamay-Tsoory et al 2010). These differences have been noted more readily in areas of the brain where white matter mylenates later in development (Herbert et al 2004(Herbert et al , 2005, and have been linked to social skills and approach in ASD (KylliĂ€inen et al 2012;Sutton et al 2005), suggesting a potential important impact of experience/environment on this progression of atypicality. Lastly, parents' retrospective reports of first concerns about autism were earlier in children with ASD with more rightdominant asymmetry versus children with ASD with a more leftdominant profile (Burnette et al 2011).…”
Section: Behavioral and Cortical Development In Adolescencementioning
confidence: 99%
“…First, and foremost, it is likely too early to judge whether a change to leftdominant asymmetry is ultimately a completely positive outcome for this population, as the literature in this area is somewhat mixed. For example, one study found that individuals with high-functioning ASD and relatively intact left-hemisphere dominance also reported more awareness of social limitations and difficulty (Sutton et al 2005). Studies have also linked left-anterior dominance with symptoms of anxious apprehension in typically developing adults (Heller et al 1997;Mathersul et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, recent theory and research suggest that several core psychological processes may be especially important in this regard. One of these involves the capacity to make attributions about the behaviors of others (Meyer et al, 2006), another involves motivational tendencies associated with approach and withdrawal (Sutton et al, 2005), and a third involves the capacity to selfmonitor goal-directed behavior . …”
mentioning
confidence: 99%